KEPUTUSAN PEMBELIAN PADA MARKETPLACE TOKOPEDIA DITINJAU DARI PENGARUH FAKTOR PROMOSI PENJUALAN, BRAND IMAGE, DAN HARGA - Ade Irawan, Indra; Kamil, Islamiah (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2022)
This study aims to analyze the effect of sales promotion, brand image, and price on purchasing decisions. The population in this study is the community of Tokopedia Marketplace users in the Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) areas. The sample used is 150 respondents. The sampling method uses Convinience Sampling. Methods of data collection using survey methods, with the research instrument is a questionnaire. The data analysis method is using Multiple Linear Regression. This study proves that sales promotion has no significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions.